2003
DOI: 10.1093/pcp/pcg070
|View full text |Cite
|
Sign up to set email alerts
|

Low-Temperature Induced Transmembrane Potential Changes in the Liverwort Conocephalum conicum

Abstract: ;Intracellular microelectrode measurements revealed that the liverwort Conocephalum conicum generates all-ornone action potentials (APs) in response to a sudden temperature drop. In plants with anion and potassium conductance blocked, dose-dependent voltage transients (VTs) were evoked by cold stimuli. These VTs did not propagate. When the external concentration of Ca 2+ was decreased or calcium channel inhibitors (La) were used, inhibition of VTs was observed. Amplitudes of both APs and VTs grew when Sr 2+ io… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
50
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 35 publications
7
50
0
1
Order By: Relevance
“…4, C and I). Such dose-dependent voltage transients may be accompanied by a transient rise in Ca 2+ permeability (Krol and Trebacz, 1999;Krol et al, 2003Krol et al, , 2004 but may not recruit sufficient Ca 2+ from internal stores to trigger a forisome response Hafke and van Bel, 2013).…”
Section: Discussion Ses Contain a Peripheral Mictoplasmic Actin Meshworkmentioning
confidence: 99%
See 1 more Smart Citation
“…4, C and I). Such dose-dependent voltage transients may be accompanied by a transient rise in Ca 2+ permeability (Krol and Trebacz, 1999;Krol et al, 2003Krol et al, , 2004 but may not recruit sufficient Ca 2+ from internal stores to trigger a forisome response Hafke and van Bel, 2013).…”
Section: Discussion Ses Contain a Peripheral Mictoplasmic Actin Meshworkmentioning
confidence: 99%
“…therein). Repolarization depends on K + -outward channels (Trebacz et al, 1994;Krol et al, 2003;Supplemental Fig. S2) identified at the plasma membrane of isolated SE protoplasts .…”
Section: Discussion Ses Contain a Peripheral Mictoplasmic Actin Meshworkmentioning
confidence: 99%
“…Early studies identified cold-induced potential changes (CIPCs) in Cucumis, Beta, and Glycine roots, Avena and Hordeum coleoptiles, Lonicera and Hedera leaves, Limnobium root hairs, and Allium epidermal cells (Minorsky, 1989). Later, a large and transient depolarization was recorded in the moss Conocephalum conicum (Krol et al, 2003) and in mesophyll cells of Arabidopsis (Arabidopsis thaliana), Helianthus annuus, and Vicia faba (Krol et al, 2004). Recently, in Arabidopsis plants expressing the calcium reporter apoaequorin in the cytoplasm (Knight et al, 1996;Plieth et al, 1999;Knight, 2002), it was found that a temperature drop of several degrees caused an immediate and transient rise in cytosolic calcium.…”
mentioning
confidence: 99%
“…Simultaneously, there are reports about intracellular investigations conducted on another liverwort Conocephalum conicum (Dziubińska et al 1983;Favre et al 1999b;Król et al 2007;Zawadzki and Trębacz 1985) and on the moss Physcomitrella patens, a species that is phylogenetically related to liverworts and regarded as a model system in plant functional genomics (Decker et al 2006;Reski 1999) and electrophysiology (Ermolayeva et al 1996(Ermolayeva et al , 1997Koselski et al 2008Koselski et al , 2013Koselski et al , 2015. Conocephalum conicum displays excitability to various stimuli, such as light (Król and Trębacz 1999;Trębacz and Zawadzki 1985;Trębacz et al 1989a), cold (Król et al 2003;Kupisz and Trebacz 2011), wounding (Favre et al 1999a), and direct current (DC) (Dziubińska et al 1983;Król and Trębacz 1999;Paszewski et al 1982). Among the stimuli mentioned above, light signals are considered as environmental factors that play a critical role in growth, reproduction, development, and regeneration, distinguishing liverworts, mosses, and other bryophytes from other plant species (Cove and Ashton 1988).…”
Section: Introductionmentioning
confidence: 99%